Innovative developments in virtual and physical prototyping : proceedings of the 5th International Conference on Advanced Research and Rapid Prototyping, Leiria, Portugal, 28 September-1 October, 2011 /: proceedings of the 5th International Conference on Advanced Research and Rapid Prototyping, Leiria, Portugal, 28 September-1 October, 2011. (©2012) - Unknown
No abstract available